Evaluation of the effectiveness of Chamomilla recutita L. in the treatment of cutaneous lesions (Research, Society and Development, 2023)
There are several ways to use complementary and integrative therapies, among which the use of Chamomilla recutita (L.) rauschert, known in popular language as chamomile, stands out. Chamomilla recutita (L.) is a plant used for therapeutic purposes since it has digestive, healing, anti-inflammatory and calming properties. In addition, this plant has several other benefits, such as: formulation of oral bases for children, treatment for chronic gingivitis, anxiolytic actions, sedative actions, hepatoprotective actions and others. It is worth mentioning that its form of extraction directly interferes with its pharmacological activity, since plant extracts can be removed and structured in different pharmaceutical forms by evaluating the efficacy, safety and quality of the active substance. Among them, we can highlight the solid forms: capsules, pills and dragees which are administered orally; Semi-solid: ointments, creams, emulsions and suppositories; and Liquids: resins, oils and the juice of the fresh parts of the plant, used for a variety of aqueous herbal preparations concentrated in fluid extracts, alcohols, tinctures, elixirs and syrups. This review aims to carry out a bibliographic survey on the main characteristics of Chamomilla recutita L. focusing on its healing actions used in the treatment of skin lesions.